Acral Plexiform Palisaded Encapsulated Neuromas as the Initial Cutaneous Manifestation of Cowden Syndrome. Issue 4 (23rd May 2017) - Harris, Elizabeth; Mir, Adnan
Abstract: Cowden syndrome (CS) is an autosomal dominant genodermatosis associated with characteristic mucocutaneous findings of facial trichilemmomas, palmoplantar keratoses, sclerotic fibromas, and oral papillomas. Mucocutaneous neuromas have also been reported in association with CS. We describe a patient with CS whose sole cutaneous finding was palisaded encapsulated neuromas (PENs) with a plexiform growth pattern in an acral location. Along with previous reports, this case suggests that acral plexiform PENs may be an early, highly specific finding in CS and highlights the importance of screening these patients for PTEN mutation.